Philosophical Questions about Teaching Philosophy: What's at Stake in High School Philosophy Education? - Norris, Trevor (Philosophical Inquiry in Education, 2015)
What is at stake in high school philosophy education, and why? Why is it a good idea to teach philosophy at this level? This essay seeks to address some issues that arose in revising the Ontario grade 12 philosophy curriculum documents, significant insights from philosophy teacher education, and some early results of recent research funded by the federal Social Sciences and Humanities Research Council (SSHRC) in Canada. These three topics include curricular disputes, stories of transformation from philosophy student to philosophy teacher, and preliminary research findings. All underscore the importance and complexity of philosophy education, as well as its challenges and benefits, including the cross-curricular benefits philosophy education imparts to the study of other subject areas. Collectively, these serve as a springboard for asking some larger and broader philosophical questions about the teaching and learning of philosophy, and they demonstrate that this is a promising new area of study and of teaching for philosophers of education. I will raise some questions about philosophy that will help frame the next stage in the SSHRC research into the teaching and learning of philosophy in Ontario, and which I contend are new and fundamental questions to ask about philosophy itself.